Thyroid-gut axis: the relationship between gut microbiota and hypothyroidism - Mota, Joseli Aparecida Braga; Silveira , Daniela Marin Machado; Silva, Rodrigo Aparecido; Pereira, Lynea Glasyele Honorato; Nascimento, Murilo Marques do Nascimento; Cabrera, Daisy Servian Cabrera; Silva, João Batista Arantes da; Melo , Raquel Nery Arantes de (Revista Brasileira de Educação e Saúde, 2025)
Objective: Systematically review recent scientific literature regarding the relationship between gut microbiota and hypothyroidism. Methods: A bibliographic search was conducted in PubMed and Frontiers databases using descriptors "gut microbiota", "hypothyroidism", "thyroid diseases", and "Mendelian randomization". Articles from the last two years directly addressing this relationship were included. Results: Eight studies were selected, demonstrating a significant association between gut microbiota alterations and the development or worsening of hypothyroidism. Reductions in short-chain fatty acid-producing bacteria, specific metabolites directly affecting thyroid function, and causal associations confirmed by robust studies were observed. Conclusion: There is a significant interaction between gut microbiota and hypothyroidism, indicating that dietary interventions targeting microbiota modulation could positively influence thyroid health, thus warranting further clinical research.